2019
DOI: 10.1002/tafs.10192
|View full text |Cite
|
Sign up to set email alerts
|

Survival under the Gravel: the Effects of Egg Size and Parental Identity on the In Situ Hatching Success of Chinook Salmon

Abstract: Early‐life mortality in salmon is influenced by both extrinsic (i.e., environmental) and intrinsic (i.e., parental) factors; however, the intrinsic factors have rarely been studied in the wild and relatively little is known about how egg mass and parental effects mediate in situ survival. Thus, we addressed four research objectives related to intrinsic factors and the early‐life survival of Chinook Salmon Oncorhynchus tshawytscha: (1) assess the effect of egg mass and parental effects on in situ hatching succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…A plausible mechanism explaining our results is that that variation in six6 alters early life survival via changes in egg composition. In oviparous species, the composition of eggs, such as hormone levels, albumin and fat content, may mediate the phenotype and behaviour of the offspring, and subsequently their fitness (Williams 1994; Thorn and Morbey 2019; Widowski et al 2022). In Chinook salmon, carotenoid composition in the eggs has been shown to be associated with early life survival (Tyndale et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A plausible mechanism explaining our results is that that variation in six6 alters early life survival via changes in egg composition. In oviparous species, the composition of eggs, such as hormone levels, albumin and fat content, may mediate the phenotype and behaviour of the offspring, and subsequently their fitness (Williams 1994; Thorn and Morbey 2019; Widowski et al 2022). In Chinook salmon, carotenoid composition in the eggs has been shown to be associated with early life survival (Tyndale et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, early incubation and rearing temperatures should affect swimming performance primarily through effects on L F or other body size traits at key developmental milestones. A salmon reared in warm water is expected to hatch and emerge with a smaller body size, both in general (Beacham & Murray, 1985, 1990 and in the focal population of the current study (Thorn & Morbey, 2019), and smaller fish generally have poorer swimming performance. In turn, poorer…”
Section: F I G U R Ementioning
confidence: 98%
“…It is also important to note that, although the theory presented here is robust, the temperature regimes used are not suitable to apply to real world situations. This is because embryo survival in laboratory conditions is typically greater than in the field (Thorn & Morbey, 2019), and the sensitivity of different species to the same environmental conditions varies substantially. Furthermore, as demonstrated by differences in survival between studies A and B, within species variation in response to similar thermal stress is observed.…”
Section: Management Implicationsmentioning
confidence: 99%